Developing a Tailored Smoking Cessation Intervention for Rheumatoid Arthritis Patients. (18th May 2015) - Aimer, Pip; Stamp, Lisa K.; Stebbings, Simon; Cameron, Vicky; Kirby, Sandra; Croft, Suzanne; Treharne, Gareth J.
Abstract: Purpose: Smoking is associated with an increased risk of comorbidities in rheumatoid arthritis (RA) and may reduce the efficacy of anti‐rheumatic therapies. Smoking cessation is therefore an important goal in RA. Our previous qualitative research identified five RA‐related barriers to smoking cessation: lack of support; limited knowledge of the relationship between smoking and RA; uncontrolled pain; inability to exercise; and using smoking as a coping strategy. The aim of this article is to describe the process of developing a smoking cessation intervention for RA patients based on these themes. Methods: A comprehensive review of the literature on smoking cessation was undertaken. A tailored smoking cessation programme was designed to address each RA‐specific barrier. A meeting was convened with key staff of Arthritis New Zealand to develop a consensus on feasible design to deliver a smoking cessation programme based on existing best practice and smoking cessation resources, and tailored within existing Arthritis New Zealand service delivery frameworks. Results: A three‐month intervention was designed to be delivered by trained arthritis educators, with the following key components: nicotine replacement therapy for eight weeks; a telephone or face‐to‐face interview with each patient to determine their individual specific RA‐related barriers to smoking cessation; and individualized education and support activities which addressed these barriers. The intervention also included three follow‐up telephone calls; a support website; and 12 weekly smoking cessation advice emails. Conclusions: A RA‐specific smoking cessation invention was developed, matching support to specific issues within each patient's experience. A pilot study is in progress to evaluate the programme's efficacy. Copyright © 2015 John Wiley & Sons, Ltd.